Mortality benefits of reduction fine particulate matter in Vietnam, 2019 - Nhung, Nguyen Thi Trang; Duc, Vu Tri; Ngoc, Vo Duc; Dien, Tran Minh; Hoang, Le Tu; Ha, Tran Thi Thuy; Khue, Pham Minh; Truong, Ngo Xuan; Thanh, Nguyen Thi Nhat; Jegasothy, Edward; Marks, Guy B.; Morgan, Geoffrey (Frontiers in Public Health, 2022)
Introduction and objectives: Studies assessing the health benefits of air pollution reduction in Vietnam are scarce. This study quantified the annual mortality burden due to PM2.5 pollution in Vietnam above the World Health Organization recommendation for community health (AQG: 5 µg/m3) and the proposed National Technical Regulation on Ambient Air Quality (proposed QCVN: 15 µg/m3). Methodology: This study applied a health impact assessment methodology with the hazard risk function for non-communicable diseases (NCDs) and lower respiratory infections (LRIs) in the Global Exposure Mortality Model (GEMM) to calculate attributable deaths, Years of Life lost, and Loss of Life expectancy at birth due to air pollution in the Vietnamese population above 25 years of age in 11 provinces. We obtained annual average PM2.5 concentrations for Vietnam in 2019 at a 3x3 km grid that was modelled using Mixed Linear regression and multi-data sources. Population and baseline mortality data were obtained from administrative data system in Vietnam. We reported the findings at both the provincial and smaller district levels. Results: Annual PM2.5 concentrations in all studied provinces exceeded both the AQG and the proposed QCVN. The maximum annual number of attributable deaths in the studied provinces if they had complied with WHO air quality guidelines were in Ha Noi City, with 5,090 (95%CI: 4,253-5,888) attributable deaths. At the district level, the highest annual rate of attributable deaths if the WHO recommendation for community health had been met was 104.6 (95%CI: 87.0-121.5) attributable deaths per 100,000 population in Ly Nhan (Ha Nam province). Conclusion: A much larger number of premature deaths in Vietnam could potentially be avoided by lowering the recommended air quality standard. These results highlight the need for effective clean air action plans by local authorities to reduce air pollution and improve community health.